Respon Pertumbuhan Rumput Pahitan (Paspalum scrobiculatum var. Commersonii) Terhadap Dosis Urea Yang Berbeda - Panuntun, Robby; Rahman Sy., A.; Alwi, Yun (Sekolah Tinggi Pertanian Kutai Timur, 2022)
This study aims to find out information about the effect of urea fertilizer on the growth of Pahitan grass (Paspalum scrobiculatum var. Commersonii). This research was carried out in Lorong Seroja, Citra Nusa Housing Block H25, Simpang 3 Sipin Village, Kota Baru District, Jambi City. The experimental design used in this study was a completely randomized design (CRD) with 5 treatments and 5 replications. The treatments used in this study were no fertilizer; 1,12 gr Urea/polybag; 2,23 gr Urea/polybag; 3,33 gr Urea/polybag dan 4,46 gr Urea/polybag Observed parameters in this study were root dry weight, number of tillers, plant height and shoot dry weight. The data obtained were analyzed using analysis of variance (ANOVA) and the variables that had a significant effect were continued with the Duncan's Multiple Range Test (DRMT). The results of the analysis of variance showed that the treatment with urea fertilizer had no significant effect (P<0.05) on the amount of Pahitan grass. However, it gave a significant effect (P>0.05) on root dry weight, plant height and crown dry weight of Pahitan grass. From the results of the research that has been carried out, it can be concluded that the application of urea fertilizer at a dose 4,46 gr/polybag increased the growth of Pahitan Grass (Paspalum scrobiculatum var. Commersonii)